2008
DOI: 10.1093/hmg/ddn070
|View full text |Cite
|
Sign up to set email alerts
|

R125W coding variant in TBC1D1 confers risk for familial obesity and contributes to linkage on chromosome 4p14 in the French population

Abstract: Stone et al. previously reported an association between the TBC1D1 gene variant R125W (rs35859249) and severe obesity in women from US pedigrees. We attempted to replicate this result in 9714 French Caucasian individuals, combining family-based and general population studies. We confirmed an association with familial obesity (defined as body mass index (BMI) > or = 97th percentile) in women from 1109 obesity-selected pedigrees (Z-score = 2.70, P = 0.008). Analysis of 16 microsatellite markers on chromosome 4 r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
69
4

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(78 citation statements)
references
References 28 publications
5
69
4
Order By: Relevance
“…By positional cloning, we previously identified a naturally occurring loss-of-function mutation in Tbc1d1 as an obesity suppressor in the lean, diabetes-resistant SJL mouse strain (10). In humans, mutations in TBC1D4 (R3633) and TBC1D1 (R125W) have been linked to severe postprandial hyperinsulinemia and obesity, respectively (11)(12)(13). TBC1D4 is found mainly in the heart, adipose tissue, and oxidative muscle fibers, whereas TBC1D1 is predominantly expressed in glycolytic skeletal muscle and is nearly absent from fat tissue (10,14,15).…”
mentioning
confidence: 99%
“…By positional cloning, we previously identified a naturally occurring loss-of-function mutation in Tbc1d1 as an obesity suppressor in the lean, diabetes-resistant SJL mouse strain (10). In humans, mutations in TBC1D4 (R3633) and TBC1D1 (R125W) have been linked to severe postprandial hyperinsulinemia and obesity, respectively (11)(12)(13). TBC1D4 is found mainly in the heart, adipose tissue, and oxidative muscle fibers, whereas TBC1D1 is predominantly expressed in glycolytic skeletal muscle and is nearly absent from fat tissue (10,14,15).…”
mentioning
confidence: 99%
“…In summary, our efforts here in using conditional Tardbp KO strategies revealed a physiological role for TDP-43 in regulating body fat and identified one specific target, Tbc1d1, a gene associated with human obesity (19,25), regulated by TDP-43. These unexpected observations indicate that TDP-43 plays a crucial role in controlling energy metabolism.…”
Section: Marked Fat Loss and High Fatty Acid Consumption In Conditionalmentioning
confidence: 93%
“…Tbc1d1, a critical protein associated with human obesity (19,25), was drastically reduced in the Tardbp deleted iTDPKO cells (−7.35 fold, P = 7.02E−228). As it has been reported that a nonfunctional Tbc1d1mutant in the skeletal muscle is responsible for the lean phenotype in mice and thatTbc1d1is essential for Glut4 translocation to the plasma membrane of skeletal muscle cells for glucose uptake (18), a decrease inTbc1d1 in skeletal muscle might offer an explanation for the lean phenotype shown in our conditional Tardp-KO mouse model (Fig.…”
Section: Marked Fat Loss and High Fatty Acid Consumption In Conditionalmentioning
confidence: 99%
See 1 more Smart Citation
“…The authors demonstrated a decrease in the expression of Tbc1d1 in mutant ES cells. Tbc1d1 is required for Glut4 translocation to the membrane of skeletal muscle cells and glucose uptake (90) and is involved in human obesity (91,92). We therefore examined TBC1D1 protein levels in hTDP-43 A315T mutants but did not detect any abnormalities in skeletal muscle or other tissues (not shown).…”
Section: A315tmentioning
confidence: 99%